Characterizing egg quality and larval performance from captive mahi‐mahi Coryphaena hippurus (Linnaeus, 1758) spawns over time. (19th August 2017) - Kloeblen, Steven; Stieglitz, John D; Suarez, Jorge A; Grosell, Martin; Benetti, Daniel D
Abstract: Mahi‐mahi Coryphaena hippurus is a promising species for aquaculture development and has been used as a model species for oil toxicology and physiology studies. This species has one of the fastest growth rates of any marine teleost and a unique reproductive biology due to its high spawning frequency and reproductive energy allocation. These characteristics lend the species to being an excellent model for understanding broodstock nutrition for other high energetic pelagic species. In this study, egg morphometrics and larval survival were tracked over a 10‐week period from the initial capture of wild mahi‐mahi broodstock. Larval quality from subsequent spawns collected over time was quantified using larval survival activity indices (SAIs) as a metric to assess egg quality. Larval SAIs were maintained and did not significantly decrease ( p < .05) over the time course of this study. A multiple linear regression based on the elapsed time in captivity of the broodstock, egg diameter and larval SAI at 1 dph provided the most accurate prediction of larval SAI at 3 dph ( R 2 = 0.996 p < .05). There were strong positive correlations with larval SAIs at 1 and 3 dph and the key nutrients: eicosapentaenoic acid (C20: 5n‐3, EPA) and related fatty acid ratios, vitamin E and nearly all amino acids under investigation. This study demonstrated that larval survival was maintained over time due to the supply of these key nutrients in the broodstock diet.